2D Materials for Fiber Lasers: Recent Advances of 2D Materials in Nonlinear Photonics and Fiber Lasers (Advanced Optical Materials 8/2020). Issue 8 (17th April 2020) - Liu, Wenjun; Liu, Mengli; Liu, Ximei; Wang, Xiaoting; Deng, Hui‐Xiong; Lei, Ming; Wei, Zhongming; Wei, Zhiyi
Abstract : In article number 1901631 by Ming Lei, Zhongming Wei and co‐workers, the application of typical 2D materials in fiber lasers is presented in detail, and the effect of layer regulation on the lasers is highlighted. Selected 2D materials have been applied, as displayed on the cover in chronological order on a time axis. The interactions between light and materials of different thickness are demonstrated.